Outcast Heroes - Ronteltap, Ferri (Fautsch Productions, 2008)
Verzio FF Submission Over a million Dalits in ‘superpower India' are caught in a vortex of severe social and economic exploitation. Behind the facade of political and economic power, however, lies an archaic society, the so-called ‘caste system'. The Dalits, formerly called Untouchables, have been struggling with caste discrimination and for their rights for the past 3000 years. They still have to deal with oppression, exclusion and violence. India is currently becoming more and more a political and economic power and Dalits are given the opportunity to fight for a dignified position in modern Indian society. However, in their struggle to exercise their human rights they are still pushed away to the margins of society. This documentary is part of ‘Change the world’, a comprehensive advocacy and awareness-raising documentary project which highlights the power of local leadership in developing countries.